To approximate solution to a problem of filtration theory for small values of TIME (Texas Journal of Engineering and Technology, 2023)
The problem of unsteady filtration, which subsequently modeled as a boundary value problem with an unknown moving boundary section. We prove the existence and uniqueness of the solution of the problem in the small.